2021
DOI: 10.1155/2021/9927699
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture as an Adjuvant Approach to Rehabilitation during Postacute Phase after Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Increasing attention has been paid to electroacupuncture (EA) for promoting postoperative rehabilitation, but the effectiveness of EA for rehabilitation after total knee arthroplasty (TKA) remains obscure. Objective. To examine the effect of EA on rehabilitation after TKA. Methods. Database searches on PubMed, CINAHL, Embase, and China National Knowledge Infrastructure (CNKI) were carried out to obtain articles, from inception to 15 October 2020. All identified articles were screened, and data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…14,15 A meta-analysis previously demonstrated that postoperative pain after TKA was reduced with the use of EA. 16 Contralateral acupuncture, also known as opposing needling or healthy side acupuncture, originally described in the Huangdi Neijing, was one of the nine needling methods described in ancient China. 17,18 In this acupuncture method, to avoid infection near the incision after TKA, traditional acupuncture point locations on the healthy side are selected for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 A meta-analysis previously demonstrated that postoperative pain after TKA was reduced with the use of EA. 16 Contralateral acupuncture, also known as opposing needling or healthy side acupuncture, originally described in the Huangdi Neijing, was one of the nine needling methods described in ancient China. 17,18 In this acupuncture method, to avoid infection near the incision after TKA, traditional acupuncture point locations on the healthy side are selected for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Electroacupuncture has shown good effects in many postoperative analgesic fields, such as pain after thoracotomy, abdominal pain after intestinal obstruction, pain after total hip replacement, pain after joint replacement, et cetera. [14][15][16][17][18] This meta-analysis will investigate the efficacy of electroacupuncture for postoperative pain in mixed hemorrhoids.…”
Section: Introductionmentioning
confidence: 99%